Malformed Information Forest - Koutsomichalis, Marinos (My University, 2020)
A series of contingent computational 3D structures, generated from the exhibition's curatorial texts or excerpts thereof, and employing Natural Language Understanding, generative solid synthesis and 3D data retrieved algorithically over the WWW.